2006
DOI: 10.1021/ic060306s
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Reactivity of Isomeric Oxo-Mn(V) Porphyrins:  Effects of Spin-State Crossing and pKa Modulation

Abstract: The reactivity of the isomeric oxo-Mn(V)-2-tetra-N-methylpyridyl (2-TMPyP) and oxo-Mn(V)-4-tetra-N-methylpyridyl (4-TMPyP) porphyrins has been investigated by a combined experimental and theoretical approach based on density functional theory. The unusual higher reactivity of the more electron-rich 4-TMPyP species appears to be related to both the higher basicity of its oxo ligand, compared to that of the 2-TMPyP isomer, and the smaller low-spin-high-spin promotion energy of 4-TMPyP, compared to that of 2-TMPy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
138
2
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(158 citation statements)
references
References 62 publications
(82 reference statements)
15
138
2
3
Order By: Relevance
“…The fast, reversible oxygen transfer reaction between Mn(III)[TDMImP] (1)/OBr À and oxo-Mn(V) [TDMImP] (2)/Br À (Scheme 1) reported here and comparisons to similar reactions of the 2-and 4-N-methylpyridyl porphyrins we have previously described [33,34] have revealed much about the mechanism of oxidative catalysis. We have shown that the rate of formation of the high-valent oxoMn(V) complex 2 increases under basic conditions whereas the reverse process, the oxygen transfer reaction to substrates, is accelerated at low pH values.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The fast, reversible oxygen transfer reaction between Mn(III)[TDMImP] (1)/OBr À and oxo-Mn(V) [TDMImP] (2)/Br À (Scheme 1) reported here and comparisons to similar reactions of the 2-and 4-N-methylpyridyl porphyrins we have previously described [33,34] have revealed much about the mechanism of oxidative catalysis. We have shown that the rate of formation of the high-valent oxoMn(V) complex 2 increases under basic conditions whereas the reverse process, the oxygen transfer reaction to substrates, is accelerated at low pH values.…”
Section: Discussionsupporting
confidence: 57%
“…Meunier et al have described the chlorination of dimedone by the water-soluble porphyrin Mn(III)TMPS supported on a polyvinylpyridinium polymer [32]. The direct oxidation of bromide by oxygen atom transfer from oxo-Mn(V) complexes has been observed in our laboratory as well as the reverse reaction, i.e., oxidation of the Mn(III) porphyrin with HOBr/ OBr À [33,34]. Recently, Naruta et al [35] reported the formation and characterization of a dinuclear oxo-Mn(V) porphyrin complex.…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…Experimental data that would provide information about the manganese-oxo bond strength only existed for oxoaqua species, such as 3, and it was consistent with the expected triple bond between manganese and oxygen (a bond order of 3). [8] The uniqueness of the most recent contribution by Groves, Spiro, and co-workers is that they have now obtained physical (spectroscopic) data for species 1 (Scheme 1) and demonstrated the relationship of the structural and electronic features with chemical reactivity. [5] In doing so, they turned their attention to the manganese complexes of the non watersoluble 5,10,15,20-tetramesitylporphyrinato dianion (TMP), and worked in acetonitrile/water solutions.…”
Section: Theintroductionintheseminal1962ballhausen-graypapermentioning
confidence: 99%
“…At pH 8 the activated porphyrin, Mn V =O, produces mainly oxygen atom transfer products while at pH 6 the products of reaction originate from electron transfer [173]. The shift in reactivity as a function of pH may be explained by the protonation state of the axial water molecule trans to the metal-oxo whose pKa value was thus estimated between 7 and 8 ( Figure 19) (for pKa2 value see [179]) …”
Section: Porphyrin Interacting With An External Gc Base-pair Of Duplementioning
confidence: 99%